Management of pediatric testicular microlithiasis - Flores, Hunter A.; Bailey, Walker C.; Harris, Kelly T. (Frontiers in Pediatrics, 2025)
Testicular microlithiasis (TM) is a primarily asymptomatic condition characterized by the accumulation of microscopic calcium deposits within the seminiferous tubules. While typically identified incidentally on ultrasonography, TM has generated clinical interest due to its potential links to infertility and testicular malignancy. TM is also associated with benign conditions like cryptorchidism, varicocele, testicular atrophy, and genetic disorders such as Klinefelter syndrome, Down syndrome, and McCune-Albright syndrome. The associations with malignancy and infertility remain poorly defined, particularly in the pediatric populations, in which diagnostic challenges and the lack of standardized surveillance protocols complicate management. This review provides an overview of the epidemiology, pathophysiology, and clinical implications of pediatric TM, with a focus on current management practices, surveillance strategies, and areas for future research.